Pengaruh Penerapan Quality Management System terhadap Kualitas Sumber Daya Manusia pada PT Casuarina Harnessindo – Bekasi - Niken Widyastuti (Universitas Proklamasi 45 Yogyakarta, 2014)
This research aim for given prove empirically effect application role of quality management system to factor or variable that influence quality human resources development. This research carry out in PT. Casuarina Harnessindo – Bekasi, with use population with amount 30 respondent with use census sample draw method: sample drawing where all population amount become sample so that amount sample within this research have amount 30 respondent. Datacollection technique use documentation and questioner. Data analysis method use research instrument test use validity test and reliability test, hypothesis test consist multiple linear regression, determinan coefficient, t testt analysis and F test, classic assumption test consist normality, multicolienearity, heteroskedasity and autocorrelation.